# How do you solve #3(2x-1)>=4(2x-3)-3#?

##### 1 Answer

Jan 2, 2017

#### Answer:

#### Explanation:

Distribute brackets on both sides of the inequality.

#6x-3>=8x-12-3rArr6x-3>=8x-15# Collect terms in x on the left side and numeric values on the right side.

subtract 8x from both sides.

#6x-8x-3>=cancel(8x)cancel(-8x)-15#

#rArr-2x-3>=-15# add 3 to both sides.

#-2xcancel(-3)cancel(+3)>=-15+3#

#rArr-2x>=-12# To solve for x, divide both sides by - 2

#color(blue)"Note"# when we multiply/divide an inequality by a negative value we must#color(blue)"reverse the inequality sign"#

#(cancel(-2) x)/cancel(-2)<=(-12)/(-2)larr" reverse sign"#

#rArrx<=6" is the solution"#